The Effect of Giving Carrot Juice and Honey to Pregnant Women in the Third Trimester on the Time of Colostrum Excretion to Increase Breastfeeding Success - Fausi, Zahira Artamevi Putri; Purnamasari, Desy; Christiana, Indah (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Breast milk production should be prepared from pregnancy, especially in the third trimester. Many pregnant women in their third trimester have not yet produced colostrum. This impacts breast milk production in the first week postpartum, thus triggering the use of formula milk. One effort to stimulate colostrum production is by consuming carrot juice and honey. This study aims to determine the effect of giving carrot juice and honey to pregnant women in their third trimester on the timing of colostrum production as an effort to achieve successful breastfeeding at Susiani Independent Midwife Practice Banyuwangi in 2025. This research method uses a quasi-experimental two-design. The study used a post-test only with a control design. The population of this study was 60 respondents, 30 of whom were in the intervention group and 30 in the control group, with consecutive sampling as the sampling technique. The intervention was administered and consumed for 7 days, twice a day. The control group was given basic IEC (Information, Education, and Communication) care for the Third Trimester. Normality and homogeneity tests were carried out, and the Levene test obtained normal values , so data analysis used the Independent Samples T-Test. The results showed that the average time for colostrum release in the intervention group was 4.87 days, with the fastest time on day 2 and the longest on day 7. In contrast, in the control group, it was 8.10 days, with the fastest time for colostrum release on day 4 and the longest on day 12. The results of the Independent Samples T-Test with a p value = 0.000 (<0.05), which means that there is an effect of giving carrot juice and honey to pregnant women in the THIRD TRIMESTER on the time for colostrum release as an effort to achieve successful breastfeeding. The results of this study will enable midwives to provide IEC on carrot juice and honey and to implement it as support for successful breastfeeding.